(untitled) - Ervina CM Simatupang; Adam Fachreza Muharam; Fauzan Basyaib; Ananda Panji Nagara; Mayil Ekataruna Harjadipura (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The purposes of this study are (1) to identify the types of idiom (2) to explain the meaning of idiom eye (s). The methods used are descriptive analysis method. The steps to obtain the data needed are as follows: identifying, classifying, analyzing the data contained in the corpus and concluding the results of the research. The theory used in this study is the theory Langlotz (2006:4) regarding the types of idioms. The results show that (1) there are three types of idiom: Transparent Idiom (36.66%), Opaque Idiom (60.34%). (2) The meaning of the eye (s) literal (0%), non-literal meaning (100%). Idioms as expressions have an indirect meaning, the meaning of which cannot be predicted. There are 30 idioms in the data. Idiom with the word eye is found in nominal group structure. It can be either as subject, object and complement. The word eye used in idiom has several meanings. The most meaning in the idiom with the word eye belongs to opaque idiom